On Spaces Within and Between: Dorota Filipczak’s (Embodied) Visions of the Sacred - Kocot, Monika (The Woman Artist: Essays in memory of Dorota Filipczak, 2024)
On the cover of her debut book of poems entitled W cieniu doskonałej pomarańczy, Dorota Filipczak shares an insight which might be treated not only as an important gateway to the realm of her poetry but also to her academic writing—“I’m passionate about the sacred in poetry and prose, and ways of its unconventional interpretation. Writing poetry and literary criticism is like looking at one and the same landscape through two separate windows” (translation mine). This essay explores a number of unconventional interpretations of the sacred in Filipczak’s poems, but it also points to similar practices in her academic writing. The image of two windows and one landscape serves as a metaphor describing the two modes of Filipczak’s writing. In order to show how this metaphor works in her poetry, I look at selected pieces from all her books of poems. In my analyses, I refer to essays by Marek Czuku and Wojciech Ligęza who focus on the link between body, mind, landscape, and myth in Filipczak’s poetry. My intention is to develop their insights and show how various metaphors of the body/body-mind are interconnected with the theme of spirituality, female empowerment, trauma and Polish history, and how they foreground the importance of places and spaces in Filipczak’s writing.